Development of an mRNA vaccine against a panel of heterologous H1N1 seasonal influenza viruses using a consensus hemagglutinin sequence - Ning Ma; Zhi-Wu Xia; Zhe-Gang Zhang; Xuan-Xuan Nian; Xue-Dan Li; Zheng Gong; Guo-Mei Zhang; Yang Le; Rong Zhou; Jia-You Zhang; Xiao-Ming Yang (Emerging Microbes and Infections)
Seasonal influenza, causes hundreds of thousands of deaths annually, posing a severe threat to human health. Currently available influenza vaccines are targeted only at specific strains or conserved epitopes; however, these vaccines are not completely efficacious because influenza viruses can undergo mutation during circulation, leading to antigenic mismatch between recommended strains and circulating strains and elusion from the immune system. Therefore, developing an influenza vaccine that is quick, effective, and broadly protective has become crucial, and the integral part of hemagglutinin (HA) remains an ideal target for vaccine development. This study developed a lipid nanoparticle-encapsulated nucleoside-modified mRNA vaccine (mRNA-LNPs) encoding a consensus full-length HA sequence (H1c) and evaluated its protective efficacy and immunogenicity through in vitro and in vivo assays. Following two intramuscular immunizations (2, 10 µg, or 20 µg) at a 3-week interval in BALB/c mice, H1c-mRNA-LNP vaccine induced strong antibodies as shown in the hemagglutination-inhibition test and protective neutralizing antibodies against numerous heterologous H1N1 influenza viruses as shown in the microneutralization assay. Additionally, both Th1- and Th2-biased cellular immune responses were elicited, with the Th1-biased response being stronger. Two doses of the H1c-mRNA-LNP vaccine could neutralize a panel of heterologous H1N1 influenza viruses and could confer protection in mice. Taken together, these findings suggest that the H1c-mRNA-LNP vaccine encoding a consensus full-length HA is a feasible strategy for developing a cross-protective vaccine against a panel of heterologous H1N1 influenza viruses.